(untitled) (Kronika Bydgoska, 2018)
The main purpose of this article is to present the history of girls’ education in Bydgoszcz during the period of the Prussian partition. The article presents elementary schools for girls, trade and continuing education schools, lower and higher level secondary schools, private educational institutions and a number of other schools and educational centers for girls.